Maxillary Impacted Second Premolar; A Surgical Intervention in an Orthodontic Case - Syed Hamza Zia; Zarnab Rizwan; Ghina Rizwan (Journal of Rawalpindi Medical College)
In clinical settings, impacted teeth are a typical occurrence. Because of their proximity to the nasal and oral cavity, impacted teeth have the potential to create more severe and catastrophic difficulties, such as the formation of dentigerous cysts and other disorders. The goal of this report is to look into the fundamentals of treating maxillary premolars that have been palatally impacted. A case report of a palatally impacted right maxillary second premolar is presented in this case report.